O papel da participaç\~ao popular na política urbana brasileira - Vanessa Gapriotti Nadalin; Daniel Pitangueira de Avelino (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The consolidation of a new legal framework for Brazilian urban policy has been emphasizing the possibility of citizen participation and social inclusion in urban policies. At the same time, current socio-spatial inequalities contribute to cities with increasingly complex problems and a reduction in the quality of life of non-privileged groups. The article tries to measure how much Brazilian urban policy has become more effective due to social participation. The theoretical and historical context of social participation in Brazil is described as well as the development of urban policies. Quantitative associations are estimated between monitoring indicators of urban policy and social participation. In general, there is evidence that social participation was not sufficient for an effective urban policy to be established, but it may have contributed to better results, at least in the area of basic sanitation.
Keywords: R5; H7; O2; 330; citizen participation; sanitation; urban policy